Nurses' experience of adjusting to workplace violence: A theory of adaptation - Chapman, Rose; Styles, I.; Perry, L.; Combs, Shane (Blackwell Publishing, 2010)
Workplace violence directed at nurses working in both the mental health and general areas of the hospital is a common occurrence and the impact of these events on all parties may be severe. A consequence of these confronting situations is the possiblitiy that nurse victims will leave the profession. To help administrators facilitate nurses' psychological recovery, this qualitative study identified how nurses in several areas of a hospital setting adapted to workplace violence. Research which has been previously unexamined. This study was the first of its kind to use a theory of cognitive adaptation to explore nurses' experiences of workplace violence. Participants were found to use the cognitive processes of finding meaning, gaining mastery and enhancing the self to adapt to workplace violence. Critical incident debriefing may facilitate the nurse victim's psychological recovery following an episode of workplace violence.